Popular cleaning systems of bottles reused for traditional food packaging in the city of Yaoundé (Cameroon) and study of their prospective effectiveness on biofilms - Mouafo, Hippolyte T.; Adjele, Jorelle J. B.; Hell, Raïssa H.; Baomog, Annick M. B.; Tchuenchieu, Alex D.; Kamgnia, Junior A. N.; Manet, Linda; Bonny, Patrice; Baleba, Roger M. M.; Medoua, Gabriel N. (Frontiers in Food Science and Technology, 2022)
This study was focused on the collecting and recycling systems of bottles reused for traditional food packaging in the city of Yaoundé and the presence of biofilms in these bottles. A cross-sectional study approved by the Institutional Review Board was conducted in 43 quarters randomly selected in Yaoundé using a semi-structured questionnaire. The target population was producers and street sellers of traditional foods who used recovered bottles for food packaging and had freely signed the informed consent clearance. Then, the recovered bottles cleaned by the participants and ready to be reused as traditional food packaging were sampled and screened for the presence of biofilms. The results showed that 84% of the 162 participants were women. Bottles reused for traditional food packaging were mainly collected from garbage (70.4%). A total of 6 different cleaning processes were identified from manufacturers of traditional food products. The cleaning processes were significantly (p<0.05) dependent on the education level and varied from one manufacturer to another. Amongst the identified cleaning processes, those which included soaking and disinfection unit operations were more efficient in biofilms’ removal. Bottles cleaned according to these processes scored the lowest biofilms’ contents. Independently of the cleaning processes, biofilms were detected in all recovered bottles. This might suggest a potential health risk for consumers.